2014
DOI: 10.1371/journal.pone.0114238
|View full text |Cite|
|
Sign up to set email alerts
|

De novo Sequencing, Assembly and Characterization of Antennal Transcriptome of Anomala corpulenta Motschulsky (Coleoptera: Rutelidae)

Abstract: Background Anomala corpulenta is an important insect pest and can cause enormous economic losses in agriculture, horticulture and forestry. It is widely distributed in China, and both larvae and adults can cause serious damage. It is difficult to control this pest because the larvae live underground. Any new control strategy should exploit alternatives to heavily and frequently used chemical insecticides. However, little genetic research has been carried out on A. corpulenta due to the lack of genomic resource… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…The data were obtained from the current study for D . valens and from references [ 7 , 20 , 24 , 91 ] for Drosophila melanogaster , [ 92 ] for Sesamia inferens ,[ 20 , 24 , 62 , 93 95 ] for Bomby mori , [ 7 , 20 , 24 , 91 ] for Tribolium castaneum ,[ 5 ] for I . typographus and D .…”
Section: Resultsmentioning
confidence: 99%
“…The data were obtained from the current study for D . valens and from references [ 7 , 20 , 24 , 91 ] for Drosophila melanogaster , [ 92 ] for Sesamia inferens ,[ 20 , 24 , 62 , 93 95 ] for Bomby mori , [ 7 , 20 , 24 , 91 ] for Tribolium castaneum ,[ 5 ] for I . typographus and D .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Illumina RNAseqs have been used for efficient assembly of de novo transcriptomes for many insects, such as Bemisia tabaci (Wang et al, 2010), Anopheles funestus (Crawford et al, 2010), and Locusta migratoria (Chen et al, 2010). Transcriptomic information is also being used in gene discovery and SSR mining (Wang et al, 2010;Li et al, 2012;Zhang et al, 2012;Chen et al, 2014). These studies indicated that Illumina deep sequencing technology can produce exceptional coverage of expressed sequences.…”
Section: Introductionmentioning
confidence: 99%
“…In H. elegans, most of the OBPs were classified as Classic OBPs, which have been found in all insect species studied (Sánchez-Gracia, Vieira & Rozas, 2009). Unlike T. castaneum, (Abdel-Latief, 2007) A. corpulenta (Chen et al, 2014) and D. ponderosae (Andersson et al, 2013) H. elegans did not show Minus-C OBPs.…”
Section: Discussionmentioning
confidence: 85%